Efek Analgesia Pemberian Lidokain 2,64% Teralkalinisasi dalam Alkohol 70% Secara Topikal Sebelum Flebotomi - Huka, Joel Apriyanto Fejacreyo; Angkejaya, Ony Wibriyono; Tuahuns, Achmad; Devi, Cokorda Istri Arintha; Hataul, Is Ikhsan; Lilihata, Jilientasia (Jurnal Anestesi Perioperatif, 2025)
Background: Phlebotomy is an essential procedure in healthcare, but it often causes pain due to its invasive nature. Although lidocaine is effective as a local anesthetic, the injectable formulation and low pH may induce pain before the anesthetic effect begins. Therefore, alkalinized lidocaine administered topically is considered a potential alternative to reduce pain and accelerate anesthetic onset. This study is essential to evaluate the effectiveness of this approach. This research aimed to assess the effect of 2.64% alkalinized lidocaine in 70% alcohol, applied topically, on phlebotomy pain levels, measured using the Numeric Rating Scale (NRS).Methods: This study employed a single-masked randomized controlled trial (RCT) with a posttest-only control group design. Samples were obtained via simple random sampling, yielding 20 paired samples from 135 eligible participants. On the first day, participants underwent phlebotomy after the application of alkalinized lidocaine, and on the tenth day, phlebotomy was repeated using 70% alcohol as the control. Pain was measured using the NRS and analyzed using the Wilcoxon test.Results: NRS scores in the control group were significantly higher than those in the experimental group, with a p-value of 0.001.Discussion: Alkalinized lidocaine effectively reduced phlebotomy pain, likely due to an increased non-ionic fraction that enhances tissue penetration and accelerates anesthetic onset. These findings align with existing literature, although generalization remains limited by the small sample size and single-masked design.Conclusion: Topically applied 2.64% alkalinized lidocaine in 70% alcohol is effective in reducing pain associated with phlebotomy.